Dampak Pembangunan Bendungan Meninting Terhadap Kondisi Sosial Ekonomi Masyarakat di Desa Bukit Tinggi Kecamatan Gunung Sari Kabupaten Lombok Barat - Rahmad Danang Prayogo; Siti Sriningsih; Adhitya Bagus Singandaru (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The growth of the creative economy in East Lombok Regency presents significant potential for creating jobs and enhancing local competitiveness. The production value in this sector serves as an important indicator for measuring the contribution of the creative economy to the overall economy, while investment plays a crucial role in driving innovation and production capacity. This study aims to analyze the impact of creative economy growth, production value, and investment on labor absorption in East Lombok Regency. This research is a quantitative descriptive study using primary data. The analysis results show that the growth of the creative economy significantly influences labor absorption, reduces unemployment, and increases community income. However, production value and investment do not demonstrate a significant effect on the welfare of workers in the region. Nevertheless, an increase in production value is expected to support the growth of the creative economy sector.